Energía 100% renovable: un compromiso mundial (2017)
The constant concern in the course of this research is to enunciate many of the aspects related to the obtaining of energy from renewable sources, which is why we must take into account associated factors that converge for the finding of these sources and that In turn, they can depend on the commitment and participation of the governments linked to the Paris 2015 agreement and also that they want to be part of this initiative.